Development of Freeware-Mobile Application for Learning Electrical Installation in Vocational High Schools - Triantini, Dewi; Supriyadi, Edy; Abubakari, Mussa Saidi (Jurnal Edukasi Elektro, 2025)
The study aims to design and develop a freeware application for electrical installation planning analysis. This research is categorized as development research, adopting the RAPID Application Development (RAD) model. The data collection process in this study involved a series of methods, including direct observation of the learning process, in-depth interviews with potential users, and the distribution of structured questionnaires to relevant respondents. The analysis of the collected data was carried out using a quantitative descriptive method, which aimed to describe and interpret numerical data related to the performance and acceptance of the developed application. The overall results of this study indicate that the designed and developed freeware application, as a learning media for electrical installation planning analysis, demonstrates highly satisfactory performance and falls into the "Very Good " category. Specifically, the evaluation of the application's functionality aspect showed a success rate of 100%, indicating that all designed features and functions operate according to the expected specifications. Similarly, the assessment of the user interface aspect also reached a percentage of 100%, implying that the application's interface design is intuitive, easy to use, and overall provides a positive user experience. In addition, in terms of material and media feasibility, it produces "Highly Feasible". The application is determined to effectively incorporate electrical installation planning content pertaining to the learning outcomes of determining cable sizes and circuit breaker capacity. Consequently, this freeware application has significant potential to become an effective learning media in enhancing the understanding and skills of students and practitioners in the field of electrical installation planning.